Traditional and additional isokinetic knee strength assessments of athletes; post-operative results of hamstring autograft ACL reconstruction - Genç, A. S.; Güzel, N. (Medicina, 2022)
Background and Objectives: Anterior cruciate ligament (ACL) injuries are common injuries in athletes, and, accordingly, ACL reconstruction (ACLR) is one of the most common orthopedic surgical procedures performed on athletes. This study aims to compare the 6-month post-operative isokinetic knee strength evaluations of the semitendinous/gracilis (ST/G) ACLR technique performed on healthy (HK) and ACLR knees of athletes.